Application of radio wave reflections from meteor showersfalling into the near-Earth space for organizing communications in the subpolar regions of the Earth - Zavjalov, S. V.; Makarov, S. B.; Lavrenyuk, I.; Aharonyan, A. K.; Avetisyan, V. H.
In this article we consider the possibilities of using organization of meteor-burst communication system in the subpolar regions of the Earth. Orthogonal frequency-division multiplexing (OFDM) signals as a general form of multi-frequency signals with amplitude limitation were applied. Optimal values of Peakto- average power ratio (PAPR) reduction were found
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture